A decomposition technique for steady-state performance evaluation of serial transfer lines subject to machine and buffer failures - Lipset, R.; Sengupta, S.; Van Til, R.P. (Proceedings of the Thirty-Third IEEE Conference on Decision and Control, 1994)
In modern automated production lines, it is common to connect pairs of machines by means of accumulating conveyors in order to provide storage and buffering between processing stations. Since conveyors are mechanical devices, they are prone to failure. Previous research in analytic modeling of the serial transfer line has assumed that buffers are completely reliable. We study the unreliable buffer, and produce a model of the serial transfer line incorporating this concept. An approximate decomposition technique is developed for the K machine serial line with unreliable buffers, and an algorithm for solution of the model is given.< >